Histone 2B (H2B) Expression Is Confined to a Proper NAD+/NADH Redox Status - Ru-Ping Dai; Fa‐Xing Yu; Shuang-Ru Goh; Hsiao-Wee Chng; Ya-Li Tan; Jian-Lin Fu; Lei Zheng; Yan Luo (2008)
S-phase transcription of the histone 2B (H2B) gene is dependent on Octamer-binding factor 1 (Oct-1) and Oct-1 Co-Activator in S-phase (OCA-S), a protein complex comprising glyceraldehyde-3-phosphate dehydrogenase and lactate dehydrogenase (p38/GAPDH and p36/LDH) along with other components. H2B transcription in vitro is modulated by NAD(H). This potentially links the cellular redox status to histone expression. Here, we show that H2B transcription requires a proper NAD(+)/NADH redox status in vitro and in vivo. Therefore, perturbing a properly balanced redox impairs H2B transcription. A redox-modulated direct p38/GAPDH-Oct-1 interaction nucleates the occupancy of the H2B promoter by the OCA-S complex, in which p36/LDH plays a critical role in the hierarchical organization of the complex. As for p38/GAPDH, p36/LDH is essential for the OCA-S function in vivo, and OCA-S-associated p36/LDH possesses an LDH enzyme activity that impacts H2B transcription. These studies suggest that the cellular redox status (metabolic states) can directly feedback to gene switching in higher eukaryotes as is commonly observed in prokaryotes.